Electrodeposited bimetallic microporous MnCu oxide electrode as a highly stable electrocatalyst for oxygen evolution reaction. (13th November 2021) - Deokate, Ramesh J.; Chavan, Harish S.; Bulakhe, Suraj C.; Tanwade, Sachin B.; Mujawar, Sarfraj H.; Mali, Sawanta S.; Hong, Chang Kook; Im, Hyunsik; Inamdar, Akbar I.
Summary: Bimetallic electrocatalysts have attracted great importance and they have proved themselves as a promising strategy for high‐performance electrocatalysis. They offer the synergetic effect between different elements and structural modification to enhance the electrochemical surface area (ECSA) and conductivity. In this study, efficient nonprecious bimetallic electrocatalysts of Mn1− x Cu x oxide (0.15 ≤ x ≤ 0.75) have been synthesized using a simple and cost‐effective electrodeposition technique. The effect of compositional ratios between Mn and Cu on the electrochemical properties has been systematically investigated. The dramatic change of morphology upon composition variation suggests the alteration of ECSA, which is an important factor for electrocatalysis. The optimized Mn0.50 Cu0.50 catalyst exhibits a low overpotential of 291 mV to reach a current density of 10 mA cm −2 with a low Tafel slope of 54.6 mV dec −1 . It showed ultra‐high stability at a very high current density of 500 mA cm −2 in alkaline media. The enhanced catalytic activity of Mn0.50 Cu0.50 electrocatalyst is associated with the enhanced ECSA, formation of porous morphology, which facilitates the diffusion coefficient, and enhanced electronic conductivity. Overall, Mn‐Cu is one of the best capable electrocatalysts for oxygen evolution reaction, which confirmed abundant potential in realistic applications. Abstract : In this work, we fabricated bimetallic Mn1− x Cu x oxide (0.15 ≤ x ≤ 0.75) thin‐film electrodes via the electrodeposition method, which is one of the easy and simple routes, and they were investigated for the oxygen evolution reaction (OER) catalyst for electrochemical water splitting. The best performing electrode exhibits an overpotential of 291 mV (vs RHE) to attain a current density of 10 mA cm −2 and the lower Tafel slope of 54.6 mV dec −1, which reveals the most favorable catalytic kinetics for mass and electron transport during the OER reaction.